HIERARCHICAL DEVELOPMENT OF PHYSICAL FRAILTY AND COGNITIVE IMPAIRMENT: CLUES INTO ETIOLOGICAL PATHWAYS. (11th November 2018) - Chu, N; Tian, J; Gross, A L; Bandeen-Roche, K; Carlson, M C; Xue, Q
Abstract: Frailty and cognitive impairment (CI) are associated and often coexist in older adults. Whether temporal patterns of occurrence reflect different etiologies remain unknown. NHATS participants were assessed annually (2011–2016) for frailty (Fried's criteria) and CI (bottom quintile of clock drawing test or immediate and delayed recall; proxy-report of diagnosis of dementia or AD8 score of >=2). We used the Fine & Gray competing risk model to identify predictive factors of frailty onset before CI, CI onset before frailty, and frailty and CI co-occurrence (within the same visit), accounting for death as competing risk. Of 7, 439 community-dwelling participants, 3, 839 (51.6%) were free of frailty and CI/dementia at baseline (median follow-up=5 years, SD=2). Incident dementia was predictive of frailty onset before CI (sub-distribution hazard ratio (SHR)=0.37, p<0.001), CI onset before frailty (SHR=2.64, p<0.001), and frailty and CI co-occurrence (SHR=8.72), p<0.001). Number of comorbidities was only strongly associated with frailty occurrence first (p<0.05).